PENGARUH MODEL PEMBELAJARAN INKUIRI DENGAN PENGGUNAAN MEDIA BERBASIS KOMPUTER (CD MOVIE DAN FLASH) TERHADAP HASIL BELAJAR KIMIA SISWA DI MA LABORATORIUM IAIN SU MEDAN - Fuadaturrahmah Fuadaturrahmah (Hijri, 2018)
As for research purposes in General is to get an idea of the influence of the use of model learning enquiries and the use of computer-based media (CD Movie and Flash) against the results of student learning. This research will be carried out in the Laboratory of the Institute of Religious Aliyah Madrasa Islamic State North Sumatra Medan. Planned research time on bulam May-June 2009/2010 lessons in year II semester of Class XI. This research will be conducted with the implementation plan of learning 3 sessions conducted at the research and may be bulai terminated in June. This research involves two classes of experiments was given different treatment. On the experimental class 1 were given preferential treatment by the granting of inkuiri learning model with computer-based media (Flash Movie and CD) while in class experiments 2 conventional learning with computer-based media (CD Movie and Flash). To find out the results of the students' creativity and studied chemistry and obtained with the application of the treatment on two students are given tests. On the basis of the findings obtained were taken the following conclusion: there is the influence of learning model inkuiri with the use of computer-based media (CD Movie and flash) and conventional learning methods with computer-based media (CD Movie and flash) against the results of the study chemistry students at the MA State Islamic Institute Laboratory in North Sumatra Province of Medan. Students who are taught with a learning model inkuiri with the use of computer-based media (CD and flash Movie) has a higher learning outcomes of the students in belajarkan with conventional learning methods with computer-based media (A flash Movie and CD).Keywords: Inkuiri Learning Computer-Based Media, The Results Of The Study